2011
DOI: 10.5194/acp-11-7375-2011
|View full text |Cite
|
Sign up to set email alerts
|

Modeling ozone plumes observed downwind of New York City over the North Atlantic Ocean during the ICARTT field campaign

Abstract: Abstract. Transport and chemical transformation of welldefined New York City (NYC) urban plumes over the North Atlantic Ocean were studied using aircraft measurements collected on 20-21 July 2004 during the ICARTT (International Consortium for Atmospheric Research on Transport and Transformation) field campaign and WRF-Chem (Weather Research and Forecasting-Chemistry) model simulations. The strong NYC urban plumes were characterized by carbon monoxide (CO) mixing ratios of 350-400 parts per billion by volume (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
1

Year Published

2012
2012
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 56 publications
2
11
0
1
Order By: Relevance
“…The tracer distribution shown is very similar to the distribution of ozone simulated by WRF-Chem (and averaged below 1700 m) that is shown in Fig. 9 of Lee et al (2011). Note that here a log scale is used to pick up the weaker concentrations further offshore.…”
Section: Tracers In the Modelsupporting
confidence: 55%
See 3 more Smart Citations
“…The tracer distribution shown is very similar to the distribution of ozone simulated by WRF-Chem (and averaged below 1700 m) that is shown in Fig. 9 of Lee et al (2011). Note that here a log scale is used to pick up the weaker concentrations further offshore.…”
Section: Tracers In the Modelsupporting
confidence: 55%
“…However, there were marked episodes of cross-coastal pollutant transport, some of which were observed by research aircraft as the air crossed the Atlantic to the Azores and Europe (Methven et al, 2006;Owen et al, 2006). Chemical processing following air masses for several days during these ICARTT Lagrangian cases has been examined in detail by Real et al (2008); Lee et al (2011);Cain et al (2012); Davis et al (2012).…”
Section: L Peake Et Al: Coastal Outflowmentioning
confidence: 99%
See 2 more Smart Citations
“…5. Lee et al (2011) simulated the first two days of transport in case 3 using WRF-Chem, a mesoscale numerical weather prediction model coupled with chemistry, run with nested domains going up to 9 km horizontal grid spacing around the eastern seaboard region, where the flight on 20 July took place. They experimented with different initial and background chemical conditions (IC/BCs), and found that their choice of IC/BCs played an important role in determining the modelled O 3 profile.…”
Section: Case 3: Low Altitude Transport From Usa To Irelandmentioning
confidence: 99%